EFEITO DE EXTRATOS AQUOSOS DE PLANTAS NO DESENVOLVIMENTO DE PLUTELLA XYLOSTELLA (L.) (LEPIDOPTERA: PLUTELLIDAE) EM COUVE - Boiça, A. l. [UNESP]; Medeiros, C. A. M. [UNESP]; Torres, A. l. [UNESP]; Chagas, N. R. [UNESP] (Instituto Biológico, 2021)
The effect of plant aqueous extracts was evaluated in the concentration of 10% on the development of Plutellax y lostella on disks of collard greens leaves, immersed in the extract. The disks were put in plates together with 12 caterpillars recently emerged, evaluating the viability and duration of the larval and pupal phases and weight of pupa after 24 hours.The larval mortality was affected by the extracts from Enterolobium contortisilliquum, Nicotiana tabacum, Sapindus saponaria and Trichilia pallida resulting in 100% of larvae mortality, followed by the extracts of T. pallida (93.8%), Azadirachta indica (89.6%), Symphytum officinale (77.1%), Bougainvillea glabra (72.9%), Achillea millefolium (70.8%) and Chenopodium ambrosioides (70.8%). The length of the larval stage varied from 8.2 days (control) to 10.7 days ( A. indica). There was direct correlation between the duration and the larvae mortality, since the extracts that induced higher mortality also increased the larval phase. Regarding the pupae weight, the biggest difference in relation to the control was observed in the treatment with the extract of B. glabra, which caused reduction of 1.2 mg. In all of the evaluated parameters, T. pallida showed higher toxicity in relation to Trichilia catigua and the branches were more poisonous than leaves in both of species, what was also observed for S. saponaria.

Avaliou-se o efeito de extratos aquosos de plantas na concentração de 10%, no desenvolvimento de Plutella xylostella, sobre discos de folhas de couve, imersos no extrato. Os discos tratados foram colocados em placas juntamente com 12 lagartas recém-eclodidas avaliando-se a viabilidade e duração das fases larval e pupal e peso de pupa após 24 horas. A mortalidade larval foi afetada pelos extratos de Enterolobium contortisilliquum, Nicotiana tabacum Sapindus saponaria e Trichilia pallida, resultando em 100% de mortalidade, seguidos dos extratos de T. pallida (93,8%), Azadirachta indica (89,6%), Symphytum officinale (77,1%), Bougainvillea glabra (72,9%), Achillea millefolium (70,8%) e Chenopodium ambrosioides (70,8%). A duração da fase larval variou de 8,2 dias (testemunha) a 10,7 dias (A. indica). Houve correlação direta entre a duração e a mortalidade de larvas, sendo que os extratos que causaram maior mortalidade, causaram também aumento na duração larval. A maior diferença no peso de pupa em relação à testemunha foi observada no tratamento com extrato de B. glabra, que causou redução de 1,2 mg. Em todos os parâmetros avaliados, T. pallida apresentou maior toxicidade em relação a Trichilia catiguae os ramos foram mais tóxicos que as folhas em ambas as espécies, diferença observada também entre as partes vegetais de S. saponaria, sendo os frutos mais tóxicos que as folhas.
FFECT OF PLANT AQUEOUS EXTRACTS ON THE DEVELOPMENT OF PLUTELLA XYLOSTELLA (L.) (LEPIDOPTERA: PLUTELLIDAE), ON COLLARD GREENS
Keywords: Insecta; Plutella xylostella; plant insecticide; Cruciferae; Insecta; Plutella xylostella; planta inseticida; Cruciferae